News on Us and Them -- reporting on Roma in public service television news - Sedláková, Renata (Romano džaniben, 2022)
What is like the presentation of the Roma in the main evening news program "Události" (Events) on Czech Television (CT), the public service TV broadcaster in CR? What are the changes in the image of the Roma created by this public service media across years 2005, 2012, and 2015? The article presents the findings of our research based on quantitative content analysis and grounded theory approach in combination with discourse analysis methods. The number of Roma-related reports in the news program barely reaches 2% of the content in all the years in focus, and the proportion of news explicitly mentioning their ethnicity is declining. Our analysis of the possible changes in the way in which Roma are referred to in the news works with the presumption that culturally shared beliefs and representations of the Others reproduced by the mainstream media testify to the majority´s selfunderstanding. A substantial part of the analysed sample of new reports worked with the opposition Us/Them, and half of the sample was framed as depicting an activity conducted by the majority, even in reports verbally or visually referring to the Romani minority. The result is an image and understanding of the Roma as passive recipients of aid and care offered by the majority. In this way stereotypes and negative connotations may be reproduced in the public broadcasting service.
Keywords: Roma; Us and Them; discourse; new racism; stereotypes; public service media; Czech Television